Influence of ionic liquids on thermodynamics of small molecule DNA interaction: the binding of ethidium bromide to calf thymus DNA - Mishra, Arpit; Ekka, Mary Krishna; Maiti, Souvik (Journal of Physical Chemistry B, 2016)
Ionic liquids (ILs) are salts with poor ionic coordination, resultantly remaining in liquid state below 100 degrees C and some may retain liquid state even at room temperature. ILs are known to provide a conducive environment for many biological enzymatic reactions, but their interaction with biomacromolecules are poorly understood. In the present study, we investigate the effect of various ionic liquids on DNA small molecule interaction using calf thymus DNA (ctDNA) ethidium bromide (EB) as a model system. The effect of various ionic liquids on these interactions is studied by an array of techniques such as circular dichroism (CD), UV melting, fluorescence exclusion and isothermal titration calorimetry. Interestingly, we observed that presence of IL increased the stability of ctDNA without altering its structure. The binding affinities Kbs for EB binding to ctDNA in the presence of 300 mM ILs are about half order of magnitude smaller than the Kbs in absence of ILs and correspond to a less favorable free energy. We noted that, when adjusted to corresponding buffer condition, the unfavorable shift in AG of ctDNA-EB interaction is attributed to decreased entropy in the case of ILs, whereas the same effect by NaCI was due to increased enthalpy.

Alternative splicing modulation mediated by G-quadruplex structures in MALAT1 lncRNA - Ghosh, Arpita; Pandey, Satya Prakash; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2022)
MALAT1, an abundant lncRNA specifically localized to nuclear speckles, regulates alternative-splicing (AS). The molecular basis of its role in AS remains poorly understood. Here, we report three conserved, thermodynamically stable, parallel RNAG-quadruplexes (rG4s) present in the 3' region of MALAT1 which regulates this function. Using rG4 domain-specific RNA-pull-down followed by mass-spectrometry, RNA-immuno-precipitation, and imaging, we demonstrate the rG4 dependent localization of Nucleolin (NCL) and Nucleophosmin (NPM) to nuclear speckles. Specific G-to-A mutations that abolish rG4 structures, result in the localization loss of both the proteins from speckles. Functionally, disruption of rG4 in MALAT1 phenocopies NCL knockdown resulting in altered pre-mRNA splicing of endogenous genes. These results reveal a central role of rG4s within the 3' region of MALAT1 orchestrating AS.

Identification of G-quadruplex structures in MALAT1 lncRNA that interact with nucleolin and nucleophosmin - Ghosh, Arpita; Pandey, Satya Prakash; Joshi, Dheeraj Chandra; Rana, Priya; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2023)
Nuclear-retained long non-coding RNAs (lncRNAs) including MALAT1 have emerged as critical regulators of many molecular processes including transcription, alternative splicing and chromatin organization. Here, we report the presence of three conserved and thermodynamically stable RNA G-quadruplexes (rG4s) located in the 3 & PRIME; region of MALAT1. Using rG4 domain-specific RNA pull-down followed by mass spectrometry and RNA immunoprecipitation, we demonstrated that the MALAT1 rG4 structures are specifically bound by two nucleolar proteins, Nucleolin (NCL) and Nucleophosmin (NPM). Using imaging, we found that the MALAT1 rG4s facilitate the localization of both NCL and NPM to nuclear speckles, and specific G-to-A mutations that disrupt the rG4 structures compromised the localization of both NCL and NPM in speckles. In vitro biophysical studies established that a truncated version of NCL (& UDelta;NCL) binds tightly to all three rG4s. Overall, our study revealed new rG4s within MALAT1, established that they are specifically recognized by NCL and NPM, and showed that disrupting the rG4s abolished localization of these proteins to nuclear speckles